2007
DOI: 10.1002/bjs.5283
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing feeding jejunostomy with nasoduodenal tube placement in patients undergoing oesophagectomy

Abstract: Nasoduodenal tube feeding is safe and efficient after oesophageal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
3
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 21 publications
6
71
3
10
Order By: Relevance
“…There are several large case series examining the use of feeding jejunostomy in oesophagectomy, some of which are summarised in Tables 5 and 6. These agree with the findings of Han-Geurts et al (2007) in relation to complication rates. Although the quality of available evidence is limited, the suggestion is that if enteral feeding is to be used post-oesophagectomy, feeding jejunostomy should be preferred over nasojejunal or nasoduodenal tubes due to its lower dislodgement rates.…”
Section: Enteral Feeding Routessupporting
confidence: 92%
See 1 more Smart Citation
“…There are several large case series examining the use of feeding jejunostomy in oesophagectomy, some of which are summarised in Tables 5 and 6. These agree with the findings of Han-Geurts et al (2007) in relation to complication rates. Although the quality of available evidence is limited, the suggestion is that if enteral feeding is to be used post-oesophagectomy, feeding jejunostomy should be preferred over nasojejunal or nasoduodenal tubes due to its lower dislodgement rates.…”
Section: Enteral Feeding Routessupporting
confidence: 92%
“…However, the follow-up period was very short (7 days), and may have missed subsequent complications. This is mirrored by Han-Geurts et al (2007) who reported a nasoduodenal dislodgement rate of 23-35%. Neither study identifies the risks associated with re-insertion of nasojejunal or duodenal tubes.…”
Section: Enteral Feeding Routesmentioning
confidence: 81%
“…Occlusion, dislocation and insertion site infection of the jejunal feeding tube occurred frequently and were comparable to rates reported in literature (0-7% occlusion, 0-11% dislocation, 1-25% infection) (9,11,12,(16)(17)(18)(19)(20)(21)(22). Previous reports also showed that severe jejunostomy-related complications requiring reoperation occur in 0-3% of all patients, which was confirmed by the present study (9,11,12,16,18,20,23). Furthermore in a randomized trial it was shown that immediate jejunostomy tube feeding may impair respiratory mechanics and may decrease mobility following esophagectomy (24).…”
Section: Discussionsupporting
confidence: 85%
“…Comparable amounts of nutrients can be applied via this route, and serious complications have not been reported (16). The only drawbacks are frequent dislocation, in 20-35% of all patients (16,25,26) and discomfort for the patient. Thus in case of an indication for long-term tube feeding, such as anastomotic leakage, a jejunostomy tube may be preferable.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports on the benefits of such an approach with some favoring a routine use 57-60 while others do not, who find nasoduodenal tubes inserted during operation to be an effective alternative. 61,62 A randomized trial of jejunostomy feeding versus intravenous fluids among patients undergoing upper GI surgery found no differences in the nutritional parameters (serum albumin, serum transferrin, serum prealbumin, weight, body fat and fat free mass) on the tenth postoperative day compared to preoperative levels between treatment groups. 63 However, institutions performing high volume esophagectomies with feeding jejunostomy as a routine adjunct find it invaluable in patients with a complicated postoperative course in whom resumption of oral feeds is delayed.…”
Section: 56mentioning
confidence: 99%